2016
DOI: 10.2196/mededu.5025
|View full text |Cite
|
Sign up to set email alerts
|

Student Response to Remote-Online Case-Based Learning: A Qualitative Study

Abstract: BackgroundCase-based learning (CBL) typically involves face-to-face interaction in small collaborative groups with a focus on self-directed study. To our knowledge, no published studies report an evaluation of Web conferencing in CBL.ObjectiveThe primary aim of this study was to explore student perceptions and attitudes in response to a remote-online case-based learning (RO-CBL) experience.MethodsThis study took place over a 2-week period in 2013 at Monash University, Victoria, Australia. A third year cohort (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 17 publications
(41 reference statements)
1
40
0
17
Order By: Relevance
“…In this period, we used PBL, RBL, CBL, and TBL methods for online teaching. Students were more satisfied with the LBL and CBL methods than with the PBL and RBL methods, which was consistent with previous studies [ 29 , 30 ]. One study [ 29 ] suggested online CBL as a potential teaching method that could be adopted during this period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this period, we used PBL, RBL, CBL, and TBL methods for online teaching. Students were more satisfied with the LBL and CBL methods than with the PBL and RBL methods, which was consistent with previous studies [ 29 , 30 ]. One study [ 29 ] suggested online CBL as a potential teaching method that could be adopted during this period.…”
Section: Discussionsupporting
confidence: 91%
“…It was found that online learning based on lectures significantly promoted the acquisition of knowledge [ 32 ]. A previous study [ 30 ] also found that online methods may be suitable to allow students to participate in CBL and that students were satisfied with the learning activity. Online teaching limited real-time eye contact and facial communication, which made teachers more uncomfortable than offline teaching [ 33 ].…”
Section: Discussionmentioning
confidence: 96%
“…In our study, we chose paper and video cases because of high feasibility and popularity of these modalities; however, it would be necessary to conduct further research to compare new modalities, such as e-CBL [38,39] and simulation-based scenarios [40].…”
Section: Pedagogical Implications Of Using Different Modalities To Immentioning
confidence: 99%
“…Otros estudios demuestran que existe hasta un 50% en disminución de los costos en comparación a la enseñanza tradicional, reduciendo el tiempo para capacitar a los maestros, gastos de viaje, gastos de trabajo y de los costos asociados a la infraestructura de la institución (Nicklen, 2016). Esto es especialmente útil en países de bajos recursos; sin embargo, para ser exitoso se requiere una inversión inicial en la formación de la infraestructura y una base de personal dedicado a mantener el campus virtual (Ramos, 2014).…”
Section: Introductionunclassified